African perspectives on researching social entrepreneurship - Farhoud Mohamed; Bignotti Alex; Hamann Ralph; Kauami Ngunoue Cynthia; Kiconco Michelle; Ghalwash Seham; De Beule Filip; Tladi Bontle; Matomela Ssanele; Kgaphola Mollette (Emera, 2025)
Purpose Context matters in social entrepreneurship, and it matters a lot. Social entrepreneurs are deeply entrenched in the context where they operate: they respond to its challenges, are shaped by it, and attempt to shape it in turn. The purpose of this paper is to discuss how social entrepreneurship in Africa is still understood within the scope of Western theories, without much consideration for local variations of the commonly shared archetype of social entrepreneurship or for how African norms, values and beliefs may shape our common understanding of this phenomenon.Design/methodology/approach The authors survey the often-neglected literature on social entrepreneurship in Africa and bring it together in this paper to discuss - also from the vantage point of their own experience and research in diverse African countries - how important assumptions in the social entrepreneurship literature are confirmed, enriched or challenged by key dimensions of African contexts.Findings Four important themes in the literature on social entrepreneurship in Africa emerged - institutions, embedding values, entrepreneurial behaviour and bricolage and scaling impact - each with its own considerations of how African contexts may challenge predominant assumptions in the extant social entrepreneurship literature, as well as implications for future research.Originality/value The authors uncover ways in which the peculiarities of the African context may challenge the underlying - and mostly implicit - assumptions that have shaped the definition and analysis of social entrepreneurship. They end by offering their understanding of social entrepreneurship and its concomitant dimensions in Africa as a stepping stone for advancing the field in the continent and beyond.